2009
DOI: 10.1111/j.1365-2788.2009.01218.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and optimal supplementation in institutionalized adults with intellectual disability

Abstract: Vitamin D insufficiency was common in adults with ID living in nursing homes. Both oral and intramuscular administrations of vitamin D3 improved vitamin D status without adverse effects. The treatment response at 6 months was better in the PO group. High-dose intramuscular vitamin D3 injections may be a convenient way to maintain sufficient vitamin D status in adults with ID but further studies are needed to establish the optimal dose and interval as well as subsequent potential health benefits in these patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Although numerous studies such as these have investigated treatment of low BMD in children [3740], relatively few studies have included adults. Since vitamin D levels are essential for normal skeletal mineralization and bone metabolism, vitamin D status was evaluated in institutionalized adults with ID in an open label trial [41]. This study compared oral and intramuscular (IM) administration of vitamin D in 138 Finnish adults with ID.…”
Section: Prevention and Treatment Of Low Bmd In Adults With D/idmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous studies such as these have investigated treatment of low BMD in children [3740], relatively few studies have included adults. Since vitamin D levels are essential for normal skeletal mineralization and bone metabolism, vitamin D status was evaluated in institutionalized adults with ID in an open label trial [41]. This study compared oral and intramuscular (IM) administration of vitamin D in 138 Finnish adults with ID.…”
Section: Prevention and Treatment Of Low Bmd In Adults With D/idmentioning
confidence: 99%
“…The plasma PTH levels decreased in both groups. This study demonstrated that vitamin D insufficiency is common in adults with ID and that either oral or intramuscular administration of vitamin D can increase mean S-25-OHD levels without adverse effects [41]. …”
Section: Prevention and Treatment Of Low Bmd In Adults With D/idmentioning
confidence: 99%
“…recommendations are to give cholecalciferol by mouth, on a daily basis, at a dose between 700 and 1000 IU [10,11]. A range of other dosages, tested in the search for regimens that would be more convenient and improve treatment adherence, are summarised in Table 3 [12][13][14][15][16][17][18][19]9].…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of at least 400 IU vitamin D orally a day, and at least 1,000 mg/day of calcium (50), antioxidants (51), and phytochemicals (52) increases capacity for physical exercises (53). …”
Section: Physical Health Promotion Prevention and Down Syndromementioning
confidence: 99%